2017
DOI: 10.1128/aac.01337-17
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitution in the Major Multidrug Efflux Transporter Protein AcrB Contributes to Low Susceptibility to Azithromycin in Haemophilus influenzae

Abstract: Clarithromycin-resistant Haemophilus influenzae strains with a nonsense mutation in acrR generally exhibited susceptibility to azithromycin, although one strain was found to be nonsusceptible; we aimed to clarify the differences. This strain had an amino acid substitution, Arg327Ser, in AcrB. Introduction of this substitution into H. influenzae Rd caused an increase in the MIC of azithromycin, suggesting that this substitution contributed to nonsusceptibility. These findings indicate that azithromycin-nonsusce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
2
4
0
Order By: Relevance
“…Deletions found in acrR of NUBL1772 were different from these reports. The results for NUBL1772 were consistent with those for H. influenzae isolates harboring AcrR with an early termination described by Seyama et al in terms of low-level acrB transcription and high efflux pump activity (22,23). Moreover, the results for NUBL1772 were consistent with those for H. influenzae isolates harboring AcrR with an early termination described by Kaczmarek et al in terms of the effect of efflux on ampicillin resistance (21).…”
Section: Resultssupporting
confidence: 87%
“…Deletions found in acrR of NUBL1772 were different from these reports. The results for NUBL1772 were consistent with those for H. influenzae isolates harboring AcrR with an early termination described by Seyama et al in terms of low-level acrB transcription and high efflux pump activity (22,23). Moreover, the results for NUBL1772 were consistent with those for H. influenzae isolates harboring AcrR with an early termination described by Kaczmarek et al in terms of the effect of efflux on ampicillin resistance (21).…”
Section: Resultssupporting
confidence: 87%
“…The rate of multidrug resistance was also significantly higher in β -lactamase-positive HI strains than in β -lactamase-negative strains. Indeed, multidrug resistance might be conveyed by transferrable plasmid conjugative resistance elements [2123].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to ampicillin resistance, H. influenzae modifies the macrolide targets (50S ribosomal RNA and ribosome-binding proteins), leading to high levels of resistance [ 66, 67 ]. This mechanism is in addition to the ubiquitously present AcrAB multidrug-efflux pump which provides a baseline reduced susceptibility, and the authors of recent studies have reported changes in the AcrAB sequence to further contribute to resistance [ 68 ]. Another major alternative are quinolones, however, recently there has been an accumulation of reports of fluoroquinolone resistance [ 69–72 ] again through mutations in the targets, DNA gyrase (encoded by gyrA and gyrB ) and topoisomerase IV (encoded by parC and parE ); and thus again conferring resistance through a plasmid-independent mechanism, making it easy for resistances to arise independently through point mutations and/or spread through recombination.…”
Section: Introductionmentioning
confidence: 99%